Perkembangan Pendidikan Indonesia Setelah Tahun 1965 Sampai Runtuhnya Orde Baru - Mauludiyah, Laila; Yafiatuzabrina, Ainiyyah; Kusmawati, Heny (Educationist: Journal of Educational and Cultural Studies, 2023)
Education is the main pillar of the founding of a nation, education is an effort to design the future of humans as a generation that advances a nation, over time the concept of education inseparable from government policy, changes occur from time to time and even increase in terms of quality but in its improvement there are also several things that need attention direct. The new order started from 1968 to 1998 when the government was led by TNI H. M. Suharto as a centralized president. Education policy during the New Order era centralization or also known as centralization. Implementation of education in the new year In the Order era, its function was transferred as a national economic instrument Development in education was carried out under bureaucratic rule administrative power. Uniformity of teaching methods and evaluation systems. Focus from This study is about the education system during the New Order era, educational excellence during the order and the lack of education during the new order. This research uses qualitative with historical research methods. . In the new order era, the system progressed,especially in primary schools, the quality of teaching staff is very poor, however the number of teachers is increasing and continuously being graduated so that the quality is maintained not as expected.